How Much Should We Weigh for a Long and Healthy Life Span? The Need to Reconcile Caloric Restriction versus Longevity with Body Mass Index versus Mortality Data - Lorenzini, Antonello (Frontiers in Endocrinology, 2014)
Total caloric restriction (CR) without malnutrition is a well-established experimental approach to extend life span in laboratory animals. Although CR in humans is capable of shifting several endocrinological parameters it is not clear where the minimum inflection point of the U shaped curve linking body mass index (BMI) with all-cause mortality lies. The exact trend of this curve, when used for planning preventive strategies for public health is of extreme importance. Normal BMI ranges from 18.5 to 24.9; many epidemiological studies show an inverse relationship between mortality and BMI inside the normal BMI range. Other studies show that the lowest mortality in the entire range of BMI is obtained in the overweight range (25 to 29.9). Reconciling the extension of life span in laboratory animals by experimental CR with the BMI-mortality curve of human epidemiology is not trivial. In fact, one interpretation is that the CR data are identifying a known: “excess fat is deleterious for health”; although a second interpretation may be that: “additional leanness from a normal body weight may add health and life span delaying the process of aging”. This short review hope to start a discussion aimed at finding the widest consensus on which weight range should be consider the “healthiest” for our species, contributing in this way to the picture of what is the correct life style for a long and healthy life span.